Estratégias de aplicação e fontes de fertilizantes na cultura da soja - Vogel, Pedro Toigo (2014)
The increased demand for agricultural products necessitates the use of precision farming tools and fertilizers properly allowing the optimization of the production space and obtaining high yields. Various fertilizers are offered in the market with different nutrients, chemical forms, particle size and efficiency. Combine operational, agronomic and economic aspect also requires studies of the strategies of fertilizer application, in order to support decision making on the use of new technologies. The study aims to evaluate the efficiency of fertilizer sources and application strategies in soybean comparing the broadcast application in surface and in the row. The study was conducted with soybean under no-tillage in crop years 2012/2013 and 2013/2014, a Oxisoil in Cruz Alta, RS. The treatments were four fertilizer sources (Factor A) and two implementation strategies (Factor B), the experimental design in randomized blocks with 4 replications. The fertilizer sources are: Microessentials S9 09-46-00; Microessentials S9 07-34-12; Monoammonium Phosphate (MAP); Formula 00-20-20, with doses adjusted so as to be maintained at the same nutritional ratio at 92 kg ha-1 for P2O5 and K2O, with the use of KCl (00-00-60) casting on the surface. The different sources were applied to the surface and haul in the row. The highest soybean are associated with the use of different fertilizers, both in the mix other materials (S9 07-34-12) as when pure (S9 9:46:00), both applied in the row as the surface haul . In 2013/2014 harvest, significant interaction of the factors. A significant different sources of fertilizers only when applied in the row effect. The higher productivity of soybean is associated with the use of the formula of S9 07-34-12 line in the row. In this formula, the dose provides differentiated amount of nutrients, in particular as to potassium, with approximately 30 kg ha-1 of K2O in the row. The lower productivity of soybeans is associated with the use of Formula 00-20-20, especially when applied in the row, probably associated with the salt effect due to high levels of potassium in the row.